HASIL BELAJAR FISIKA PESERTA DIDIK MELALUI PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E BERBANTUAN PETA KONSEP KELAS XI SMAIT AL-FITYAH PEKANBARU - Ariyanto, Delvian; Azhar, Azhar; Ma’ruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to describe the physics learning of student’s outcomes through the implementation of learning cycle 5e with concept map in class XI SMAIT Al-Fityah Pekanbaru. The research method used is Pre-Experimental by using The One-Shot Case Study design. The time of this research was conducted at in November until December 2018. Subject of this research was class XI (Al-Fath) student consisting of 20 students. The data in this study is the results of student's learning outcomes test in the form of multiple choice to 15 questions. The data analysis used is descriptive analysis that is by determining the absorption and effectiveness of learning. Based on data analysis, the result shows that the average absorption of students is 81% which is in good category and effectiveness of learning analysis which is in effective category to fluida dinamik concept. The coclusion implementation of learning cycle 5e with concept map is effective in class XI SMAIT Al-Fityah Pekanbaru.Key Words: Physics Learning Outcomes, Implementation Of Learning Cycle 5e With ‘ Concept Map